Motivation Level of Grade VI Students during Online Learning - Tiauw, Victoria (JPGI (Jurnal Penelitian Guru Indonesia), 2022)
The learning process of all students around the world has undergone drastic changes due to the COVID-19 pandemic. School R handles it like most other schools, by distance learning through online learning. This change may cause [H1] students to feel unmotivated in studying compared to face-to-face learning. The purpose of this study was to measure the level of motivation of grade VI students in school R in Mathematics. The research method uses the Motivation Questionnaire (MQ) questionnaire. MQ adopts indicators from the Motivated Strategies for Learning Questionnaire (MSLQ). After the MSLQ was analyzed and edited, the MQ instrument was designed to suit the sixth-grade students of R school. The results of the study showed that more than 50% of students scored lower than the average score in the value and expectancy components (57.14% and 51.02% respectively), and more than 50% of students scored higher than the average score in the affective component (55.10%). Test-retest was conducted to analyze the reliability by analyzing the Pearson Correlation Coefficient and the result was 0.771. This indicates that the correlation between test-retest results is strong. The results of the Cronbach alpha analysis for the MQ of each sample from the test-retest were 0.888 and 0.911, indicating strong internal consistency. The validity of the questionnaire study [H2] uses peer review and expert judgment. In conclusion, the level of motivation of the research subjects tends to be low. One suggestion to overcome this problem is a greater involvement of the role of educators. Educators must strive to be creative in teaching, increase interaction with students and respond quickly. In addition to educators, parents and educational organizations can also provide more support to increase students’ motivation in learning. [H1]may cause (?) [H2]the questionnaire